2020
DOI: 10.1159/000511093
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profile of Cardiovascular Risk in Patients with Obstructive Sleep Apnea

Abstract: <b><i>Background:</i></b> Obstructive sleep apnea (OSA) is a common disease caused by repeated episodes of collapse of the upper airway during sleep and is associated with the development of cardiovascular disease (CVD). However, there is high heterogeneity in the impact of OSA on patients. Until now, the profile of OSA patients at risk of developing CVD has not been defined, including the measurable variables that could be used to predict the CVD risk of a patient with OSA. <b>&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…MiR-486-5p has been revealed to have protective effects in cardiovascular and cerebrovascular diseases [ 17 , 24 ]. In patients with high blood pressure, significantly reduced miR-486-5p has been detected, which shows a close association with the cardiovascular risk score [ 17 ]. In addition, decreased exosomal miR-486-5p is related to antiangiogenesis in refractory intracranial atherosclerosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-486-5p has been revealed to have protective effects in cardiovascular and cerebrovascular diseases [ 17 , 24 ]. In patients with high blood pressure, significantly reduced miR-486-5p has been detected, which shows a close association with the cardiovascular risk score [ 17 ]. In addition, decreased exosomal miR-486-5p is related to antiangiogenesis in refractory intracranial atherosclerosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-486-5p is one of the important miRNAs with high abundance expression in the heart, downregulation of miR-486-5p has been detected in coronary atherosclerotic plaques via microarray experiments [ 16 ]. In addition, significantly reduced miR-486-5p is detected in individuals with high blood pressure, which shows a significant association with the cardiovascular risk score [ 17 ]. These results demonstrate the important influence of miR-486-5p on arteriosclerosis, which encourages us to explore its role in CAS.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the utility of miRNAs as potentially useful biomarkers for personalized management of OSA 9 , 10 , 25 , 26 . Previous studies from our group identified a set of miRNAs that act as ECs in male patients with OSA 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The level of miR-486 elevated in the blood of patients with CAD [151] and is associated with the risk of developing cardiovascular diseases [109,206].…”
Section: Mir-378 Abcg1mentioning
confidence: 99%